A nonlinear model-based control method for magnetostrictive actuators - Smith, R.C. (Proceedings of the 36th IEEE Conference on Decision and Control, 1997)
A nonlinear model-based control method for magnetostrictive actuators is presented in this paper. Such actuators utilize the realignment of magnetic moments in response to applied magnetic fields to generate strains in the material. Strains and forces generated in this manner are significantly larger than those produced by many other smart materials but also exhibit significant nonlinearities and hysteresis. To utilize the full potential of these materials in control transducers, these inherent nonlinearities and hysteresis must be accurately characterized and incorporated in the control law. An energy-based model is employed to characterize the hysteresis in a manner amenable to structural applications. Nonlinear optimal control theory is then used to determine appropriate inputs to the system. The effectiveness of this nonlinear model-based control method is demonstrated through a numerical example.